Careers in serious leisure : from dabbler to devotee in search of fulfilment - Stebbins, Robert A. (Palgrave Macmillan, 2020)
Using the concept of fulfilment and the framework of the serious leisure perspective, this book examines the signposts marking the fulfilment career. This career begins with an interest in a serious pursuit, leading to an efflorescence many years later in amateurism, hobbyism, volunteering, or devotee work - and ultimately deeper fulfilment.